2023
DOI: 10.3389/fcimb.2023.1170326
|View full text |Cite
|
Sign up to set email alerts
|

Structure of gut microbiota and characteristics of fecal metabolites in patients with lung cancer

Abstract: ObjectiveThe gut micro-biome plays a pivotal role in the progression of lung cancer. However, the specific mechanisms by which the intestinal microbiota and its metabolites are involved in the lung cancer process remain unclear.MethodStool samples from 52 patients with lung cancer and 29 healthy control individuals were collected and subjected to 16S rRNA gene amplification sequencing and non-targeted gas/liquid chromatography-mass spectrometry metabolomics analysis. Then microbiota, metabolites and potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…An increasing body of studies have shown that the GM may be involved in the development and progression of various types of cancer, such as breast cancer [27], gastrointestinal cancer [28] and lung cancer [29]. LUAD is the most common subtype of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing body of studies have shown that the GM may be involved in the development and progression of various types of cancer, such as breast cancer [27], gastrointestinal cancer [28] and lung cancer [29]. LUAD is the most common subtype of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies showed the important role of gut microbiota (GM) in LC pathogenesis and treatment. The results from Lu et al showed that Ruminococcus gnavus was significantly upregulated in LC patients, with Firmicutes, Clostridia, Bacteroidacea, Bacteroides, and Lachnospira being enriched in the healthy population [9]. Lee et al showed that bifidobacterium could improve sensitivity to immune checkpoint inhibitors (ICIs) in non-small cell lung cancer (NSCLC) patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a growing body of research suggests an inseparable relationship between the occurrence and development of adult tumors and the gut microbiota. For instance, resident gut bacteria can influence patients' response to cancer immunotherapy ( 23 ), the gut microbiota possesses a unique ability to influence the tumor microenvironment as well as the metabolism of chemotherapy drugs or medications ( 24 ), the gut microbiota can modulate melanoma patients' response to PD-1 immunotherapy ( 25 ), the gut microbiota and its metabolites change with different stages of lung cancer development ( 26 ), the composition of the gut microbiota in patients diagnosed with colorectal cancer differs significantly from that of healthy individuals ( 27 ), based on specific changes in the gut microbiota, it is possible to screen for gut microbiota-targeted biomarkers and establish a diagnostic model, potentially serving as a non-invasive tool for distinguishing hepatocellular carcinoma ( 28 ), However, many aspects, including the mechanisms of onset, age of onset and characteristic features, differ between pediatric tumors and adult tumors. For instance, compared to adult tumors, childhood tumors generally exhibit a lower overall mutation burden ( 9 ).…”
Section: Introductionmentioning
confidence: 99%